2014
DOI: 10.1007/s11920-014-0495-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Older Adults: The Role of Emotions and Cognition

Abstract: Suicide in older adults is a significant clinical concern. In this review of recent findings, we concentrate on the role of emotions and cognition in suicide risk and behavior in older adults. We discuss the epidemiology of suicide in older adults, integrate recent findings on non-psychotic major depression, schizophrenia and suicidal ideation, explore the relationship of emotion regulation with suicide, present recent advances on suicide in demented patients, and describe the latest developments on cognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 82 publications
2
36
2
7
Order By: Relevance
“…It is well known that ethnicity, age, gender and cognitive burden are risk factor for late life suicidality[41, 42]. While younger age predicted improvements at 36 weeks, gender, ethnicity and cognition did not predict changes in suicidal ideation at any time point.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that ethnicity, age, gender and cognitive burden are risk factor for late life suicidality[41, 42]. While younger age predicted improvements at 36 weeks, gender, ethnicity and cognition did not predict changes in suicidal ideation at any time point.…”
Section: Discussionmentioning
confidence: 94%
“…A more fine-grained interpretation of the studies described as measuring executive functioning above reveals older adults at risk for suicide are characterized by deficits in cognitive control (associated with high-lethality suicide attempts), deficits in decision-making (associated with lower lethality impulsive suicide attempts), and deficits in social cognition and social decision making (for a review, see Kiosses, Szanto, & Alexopoulos, 2014). One recent study using fMRI (Vanyukov, et al, 2014) found that greater impulsivity in social problem solving, as well as the presence of past unplanned suicide attempts, were associated with increased activation in the prefrontal cortex when viewing angry faces, suggesting that socioemotional stimuli are processed differently among older adults with impulsive suicide attempts.…”
Section: Cognition and Cognitive Impairmentmentioning
confidence: 99%
“…Conwell, Van Orden, and Caine (2011) reported in a review that depression had been identified in up to 97% of suicide deaths in older people. Meanwhile, loneliness and anxiety were found associated with suicidal ideation in older people with depression (Kiosses et al, 2014).…”
Section: The Impact Of Loneliness Anxiety and Depression In Older Pementioning
confidence: 98%
“…A literature review found that depression was the common mental disorder present in most suicides carried out by older people (Kiosses, Szanto, & Alexopoulos, 2014). Conwell, Van Orden, and Caine (2011) reported in a review that depression had been identified in up to 97% of suicide deaths in older people.…”
Section: The Impact Of Loneliness Anxiety and Depression In Older Pementioning
confidence: 99%
See 1 more Smart Citation